The intern - Campbell, Michele, 1962- (St. Martin's Press, 2023)
"Madison Rivera lands the internship of a lifetime working for Judge Kathryn Conroy. But Madison has a secret that could destroy her career. Her troubled younger brother Danny has been arrested, and Conroy is the judge on his case. When Danny goes missing after accusing the judge of corruption, Madison's quest for answers brings her deep into the judge's glamorous world. Is Kathryn Conroy a mentor, a victim, or a criminal? Is she trying to help Madison or use her as a pawn? And why is somebody trying to kill her? As the two women circle each other in a dangerous cat-and-mouse game, will they save each other, or will betrayal leave one of them dead?"--